Engineering geology of waste disposal - Bentley, Stephen P. (Geological Society engineering geology special publication, 1996)
This volume covers a wide spectrum of activities in the field of waste disposal. These activities range from design of new landfills and containment properties of natural clays to investigation, hazard assessment and remediation of existing landfills. Consideration is given to design criteria for hard rock quarries when used for waste disposal. In addition, an entire section concerns the geotechnics of underground repositories. This covers such topics as deep drilling, in situ stress measurement, rock mass characterization, groundwater flows and barrier design.